Analysis of Islamic Rural Banks Efficiency in the East Region of Indonesia - Salama, Sri Cahyaning Umi (Universitas Airlangga, 2022)
Islamic Rural Bank (BPRS) has important roles for micro-enterprises in Indonesia. This study analyzes the performance of Islamic Rural Bank in Eastern Indonesia, where the Muslim population is minority. Using 14 BPRS spread across a number of islands in Eastern Indonesia with a five-year vulnerability (2016- 2020) and using the Data Analysis Envelopment (DEA) Variable Return to Scale (BCC) model, it can be concluded that only 4 Islamic Rural Banks have been able to be efficient for five consecutive years. -consistent even during a pandemic. Meanwhile, 2 Islamic Rural Banks have not been able to work efficiently for five years and the remaining 8 Islamic Rural Banks are still not consistently working efficiently. During the pandemic, 70% of Islamic Rural Banks that were efficient in the previous year were able to operate efficiently, while 30% of BPRS that were efficient in the year before the pandemic were unable to work efficiently. It is also known that all Islamic Rural Banks that were not efficient in the year before the pandemic remained inefficient during the pandemic.